2009
DOI: 10.1155/2009/193260
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Frequency Low‐Intensity Ultrasounds Do Not Influence the Survival and Immune Functions of Cultured Keratinocytes and Dendritic Cells

Abstract: Low-frequency ultrasounds (US) are used to enhance drug transdermal transport. Although this phenomenon has been extensively analyzed, information on US effects on the single skin cell components is limited. Here, we investigated the possible effects of low-frequency US on viability and immune functions of cultured human keratinocytes and dendritic cells (DC), skin cells involved in the regulation of many immune-mediated dermatoses. We demonstrated that US, employed at low-frequency (42 KHz) and low-intensity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…In fact, LFS alone, in the absence of antigen, was found to induce activation of Langerhans cells in these studies 31. Other studies have also shown the ability of high-amplitude LFS (5–7 W/cm 2 ) to induce an increased immune response, when compared to low-amplitude LFS (0.15 W/cm 2 ) and negative controls 70. These findings demonstrate the significant potential of LFS to act as a physical adjuvant, and motivate further investigation of LFS-mediated transdermal immunization.…”
Section: Delivery Of Macromolecules Utilizing Lfssupporting
confidence: 51%
See 1 more Smart Citation
“…In fact, LFS alone, in the absence of antigen, was found to induce activation of Langerhans cells in these studies 31. Other studies have also shown the ability of high-amplitude LFS (5–7 W/cm 2 ) to induce an increased immune response, when compared to low-amplitude LFS (0.15 W/cm 2 ) and negative controls 70. These findings demonstrate the significant potential of LFS to act as a physical adjuvant, and motivate further investigation of LFS-mediated transdermal immunization.…”
Section: Delivery Of Macromolecules Utilizing Lfssupporting
confidence: 51%
“…As stated above, the SonoPrep® has therefore been FDA approved for use in children and adults for decreasing the onset time to local anesthesia. The effect of LFS on animal models and cultured cell lines has also shown that the use of low ultrasound intensities is safe, causing no changes in skin pathology and cell viability 19, 22, 26, 70, 79. In general, for single application treatments, thermal effects caused by LFS are of most consequence to the skin if not monitored properly, causing potentially serious side effects such as burns, epidermal detachment, epidermal or dermal necrosis, and, on a cellular level, keratinocyte apoptosis 70, 79.…”
Section: Safety Of Lfsmentioning
confidence: 99%
“…Although SDT is a promising approach because of its noninvasive and deeper penetration properties compared to surgery or light in PDT, the clinical application of a photosensitizer must overcome the potential problems mentioned above. Many recent reports concerning SDT have focused on apoptotic events after ultrasound irradiation with a photosensitizer in vitro [19][20][21]. However, the efficacy of SDT or whether it has any advantages over PDT has not yet been rigorously tested in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…The bubbles become unstable as a result of large local pressure gradients, and implode. This results in a jet of liquid that can penetrate the SC [25], [26]. Cavitational effects are inversely correlated with US frequency, making LFS the most efficient for permeabilization [27].…”
Section: Techniques For Skin Permeabilizationmentioning
confidence: 99%
“…The live keratinocytes directly below the SC also serve a protective function. Upon insult, keratinocytes are able to secrete cytokines and chemokines to stimulate immune function at the site of infection [26]. This signaling can recruit patrolling dendritic cells.…”
Section: Introductionmentioning
confidence: 99%